Hybrid Solar/Heat Pipe/Water Heater - Lau, Jin Yik (2015)
The performance of a hybrid solar/ heat pipe/ water heater were investigated the system conversion of an array individual evacuated tube heat pipe solar collector (ETHPSC) exposed to sunlight, four thermoelectric (TE) modules are placed on the outer surfaces of the aluminum block and four units of water cooled jackets are placed over the TE modules. The jackets are thin aluminum composite slabs with parallel internal water flow channels connected by inlet and outlet headers inside the slabs. The experiment result showed that water can be heated with a temperature difference of around 0.3C – 7.6C.